Your child's strengths : discover them, develop them, use them - Fox, Jenifer (New York : Viking, 2008)
A book for parents and teachers that explores how children's individual strengths create success. Educator Fox is poised to change the conversation about education in this country. For too long, parents and teachers have focused on identifying and "fixing" kids' weaknesses--this book turns that flawed paradigm on its head. Fox's strengths-based philosophy provides the tools to prepare kids for the future in a world that demands greater adaptability and creative thinking than ever before. She gives parents and teachers the tools to discover strengths in three main areas working in tandem: Activity Strengths, the tasks that make us feel engaged and energized; Relationship Strengths, the things we do for and with others that make us feel valued and competent; and Learning Strengths, the ways we approach and understand new information. This book is a road map for young people and society to a future that plays to strengths.--From publisher description.
Includes index.
Keywords: Child development; Ability in children; Child rearing; Teaching; Education -- Parent participation